Microbiological and Compositional Characteristics of Çeçil Cheese Collected from Households in Erzurum, Turkey - DIKBAS†, NESLIHAN; SENGÜL*, MUSTAFA; FATIH ERTUGAY, M. (Asian Journal of Chemistry, 2024)
The objective of this work is to determine the microbiological andchemical characteristics of Çeçil cheese. A total of 15 samples of Çeçilcheese were collected from individual households in Erzurum, Turkey.In the samples, average of total aerobic mesophilic bacteria, yeast andmoulds, lactic acid bacteria (LAB) and Staphylococcus aures were determinedto be 1.6 × 106, 7.0 × 104, 1.8 × 105, 6.4 × 102 cfu/g, respectively.Coliform bacteria were lower than < 10 cfu/g in 86.66 % of the samples.On the other hand, the coliform positive samples showed an average of8.5 × 101 cfu/g. S. aureus were not detected in 46.66 % of Çeçil cheesesamples. One hundred and eighteen strains of lactic acid bacteria isolatedfrom Çeçil cheese were identified. Three genera were found: Lactobacillus(88.13 %), Leuconostoc (5.93 %) and Pediococcus (5.93 %). Lacticacid bacteria dominated the microflora of these samples, especially thegenera Lactobacillus. The dominant Lactobacillus species were Lb.coryniformis subsp. coryniformis (36 strains), Lb. brevis (29 strains).In Çeçil cheese samples analyzed, dry matter, fat, salt, total nitrogen,pH, titratable acidity and ash values were found between 34.80 and59.30 g/100 g cheese, 2.0 and 14.0 g/100 g cheese, 5.49 and 15.09 g/100 gcheese, 13.40 and 31.70 g/100 g cheese, 5.35 and 4.92, 0.32 and 1.05 %,9.37 and 18.50 g/100 g cheese, respectively.